Mathematical Literacy Problems in Exponential Material Based on Vocational Students’ Self-Regulated Learning - Pratiwi, Yolanda; Kusno, Kusno; Subekti, Fitrianto Eko (Jurnal Pendidikan Matematika (JUPITEK), 2025)
This study explores the mathematical literacy challenges faced by students at SMK Negeri 2 Bawang, Banjarnegara Regency, in learning exponential concepts, which are analyzed through the lens of the Independent Regular Learning (SRL) level. Using a descriptive qualitative approach, this study involved three student subjects representing high, medium, and low SRL categories. Data was collected through mathematical literacy tests, SRL questionnaires, and interviews. The research findings indicate that variations in SRL levels significantly influence the types of difficulties students experience. Students with low SRL face various challenges, including understanding the context of the problem, building mathematical models, and interpreting results. Students with moderate SRL demonstrate the ability to understand problems but have difficulty selecting appropriate problem-solving strategies and accurately representing contextual situations in mathematical form. Meanwhile, students with high SRL exhibit systematic and reflective thinking but encounter obstacles connecting mathematical outcomes to real-life contexts. These findings underscore the role of SRL in shaping students' mathematical literacy challenges. Further research is recommended to investigate additional internal factors that influence mathematical literacy in order to develop more adaptive and targeted teaching strategies